2013
DOI: 10.1017/s0317167100015900
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Delayed Radiation Therapy on Patients with Glioblastoma

Abstract: 790Glioblastoma is the most prevalent and aggressive primary malignant brain tumor in adults.1 Since the publication of Stupp et al., the standard of care for the treatment of glioblastoma includes maximal surgical resection followed by radiation therapy (RT) and concomitant and adjuvant temozolomide treatment. Despite the use of this state-of-the-art treatment regimen, the median survival time of patients with glioblastoma is only 14.6 months.1 Well-established favorable prognostic factors include the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Since several studies suggested that there is a possible impact on survival when starting RT prematurely or with a significant delay, and although not our primary analysis goal due to important biases, we also conducted a survival analysis for the small subsets of patients that received RT earlier than 14 days or after 48 days postoperatively [14, 16, 22, 35, 41, 42]. A significantly shorter OS was shown for the patients that started RT after a prolonged delay.…”
Section: Discussionmentioning
confidence: 99%
“…Since several studies suggested that there is a possible impact on survival when starting RT prematurely or with a significant delay, and although not our primary analysis goal due to important biases, we also conducted a survival analysis for the small subsets of patients that received RT earlier than 14 days or after 48 days postoperatively [14, 16, 22, 35, 41, 42]. A significantly shorter OS was shown for the patients that started RT after a prolonged delay.…”
Section: Discussionmentioning
confidence: 99%
“…Do et al [18] used multivariate analysis to assess the effect of radiotherapy delay on survival in a retrospective study of 182 patients with high-grade glioma and found no significant effect of delaying postoperative RT on OS. However, some other retrospective analyses found a significant unfavorable effect of shorter delays on OS [19] , [20] , [21] . Wurschmidt et al [22] assessed the importance of time interval between surgery and postoperative RT in non–small-cell lung carcinoma; controlling the status of resection margins and performance status, they found that the 175 patients who were irradiated at <36 days after surgery had a significantly detrimental survival compared with the 165 patients irradiated at ≥36 days after surgery.…”
Section: Discussionmentioning
confidence: 90%
“…17,18 Several observational studies with up to 2,388 patients published beneficial effects for either early initiation of irradiation after surgery [19][20][21] or postponed adjuvant therapy. [22][23][24][25][26] Possible explanations for the necessity of either early or late adjuvant irradiation were discussed before. This includes early radio-insensitivity due to postoperative hypoxia, 22 higher brain tissue damage in early irradiation, 27 or increased side effects by larger radiation fields due to an uncollapsed resection cavity.…”
Section: Discussionmentioning
confidence: 99%